The Influence of English on Italian Lexical and Cultural Features - Pulcini, Virginia (Language Contact and Bilingualism [LCB], 2023)
The volume explores the history of language contact between Italy and Anglophone countries and illustrates the phenomenon of lexical borrowing. Types of borrowings are discussed on the basis of a usage-based list of Anglicisms, which is part of a multilingual project (GLAD - Global Anglicism Database). It is addressed to scholars and non-experts interested in the input of English words into Italian.